Semi-Empirical AM1 and PM3 Calculations for Electronic Structure of a Pyrazolone - Arora, Kishore; Kumar, D. (Asian Journal of Chemistry, 2010)
Pyrazolones and substituted pyrazolones are widely in use for the synthetic purposes. These are stable compounds, which are in use for synthesis of many complexes like complexes of transition metals, thorium(IV) and dioxouranium(VI) metals. Experimental data for this compound is available, so it prompted us to study the electronic structure of this compound using semi-empirical AM1 and PM3 quantum chemical calculations. The theoretical study reveals that it is the carbonyl group of the pyrazolone under study which act as a site for coordination to metal as it is reported by the experimental chemist.